Nano Tips for Using AI in the Job Search with Sho Dewan. - Dewan, Sho (linkedin.com, 2023)
Get quick, bite-sized tips to leverage the power of AI on a job search. Each video is less than two minutes long, so you can make learning fit into even your busiest days.